Psikologis yang Kronis Para Tokoh Sentimentalisme Calon Mayat: Psikoanalisis Freudian - Rafi Ferdiansyah; Jiphie Gilia Indriyani (Faculty of Letters Universitas Balikpapan, 2023)
Sony Karsono's short story as an absurd and obscure literary product turns out to have a human message that is rarely known by the public. This article only uses Sentimentalisme Calon Mayat, Melankoli, and Insomnia. The three short stories present various mental problems: from the Oedipus complex, to sexual aversion disorder, to agalmathophobia. This phenomenon is caused by activities that are commonly known by the public, such as the lack of a father's approach to his child, sexual problems by men, and a woman's mood swings. Finally, the impact of phenomena like this shows a dangerous condition, such as suicide, cutting genitals, to feel proud to be married and have children with dolls. This article utilizes the Freudian psychoanalytic paradigm as its study. Freud believed that the good or bad of a person's activity is determined by how big the problem he is facing.